Vancomycin-loaded silk fibroin microspheres in an injectable hydrogel for chronic osteomyelitis therapy - Zhang, Peng; Sun, Yusheng; Yang, Haizhen; Liu, Dong; Zhang, Feng; Zhang, Yu; Zhong, Wentao; Zuo, Baoqi; Zhou, Zhiqiang (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Chronic osteomyelitis remains a clinical challenge in orthopedics. Methods: In this study, silk fibroin microspheres (SFMPs) loaded with vancomycin are entrapped in an injectable silk hydrogel to form a vancomycin delivery system for treatment of chronic osteomyelitis. Results and Discussion: Vancomycin showed continuous release from the hydrogel for up to 25 days. The hydrogel shows strong antibacterial activity against both Escherichia coli and Staphylococcus aureus and a long antibacterial duration of 10 days without a decrease in the antibacterial effect. The injection of vancomycin-loaded silk fibroin microspheres entrapped in the hydrogel into the infected site of rat tibia reduced bone infection and improved bone regeneration compared with other treatment groups. Conclusion: Thus, the composite SF hydrogel features a sustained-release profile and good biocompatibility, making it promising for application in osteomyelitis treatment.